2022
DOI: 10.1007/s00213-022-06191-9
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent self-administration of the synthetic cannabinoid receptor agonist JWH-018 induces neurobiological and behavioral alterations in adult male mice

Abstract: Rationale The use of synthetic cannabinoid receptor agonists (SCRAs) is growing among adolescents, posing major medical and psychiatric risks. JWH-018 represents the reference compound of SCRA-containing products. Objectives This study was performed to evaluate the enduring consequences of adolescent voluntary consumption of JWH-018. Methods The reinforcing properties of JWH-018 were characterized in male CD1 adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 104 publications
2
8
0
Order By: Relevance
“…Notably, adolescent JWH-018 exposure induced an activation of microglia and astrocytes in the prefrontal cortex of adult male mice. In agreement, a recent study showed a long-term microglia activation in several brain areas such as the nucleus accumbens and caudate-putamen following adolescent self-administration of JWH-018 [ 43 ]. Taken together, it is tempting to hypothesize that exposure to JWH-018 to adolescent mice induces changes in glial cells reactivity and PNNs density in the prefrontal cortex, leading to the appearance of sensorimotor gating deficits in adulthood.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Notably, adolescent JWH-018 exposure induced an activation of microglia and astrocytes in the prefrontal cortex of adult male mice. In agreement, a recent study showed a long-term microglia activation in several brain areas such as the nucleus accumbens and caudate-putamen following adolescent self-administration of JWH-018 [ 43 ]. Taken together, it is tempting to hypothesize that exposure to JWH-018 to adolescent mice induces changes in glial cells reactivity and PNNs density in the prefrontal cortex, leading to the appearance of sensorimotor gating deficits in adulthood.…”
Section: Discussionsupporting
confidence: 79%
“…By using the EPM, most of the studies have not shown differences in anxiety in adult male [ 24 , 40 , 41 ] or female [ 40 , 41 ] rodents due to adolescent ∆ 9 -THC exposure, although an anxiogenic-like effect was observed in adult male mice in another report [ 42 ]. A recent study revealed an increase of repetitive/compulsive behaviors at adulthood in adolescent male mice exposed to JWH-018, as shown in the nestlet shredding and marble burying tests [ 43 ]. Although marble burying test can be used to assess anxiety-like behavior, the heightened marble burying activity of JWH-018 treated male mice could reflect compulsive-like rather than anxiety-like states considering that in a previous study adult male rats showed increased burying scores, but not anxiety alterations in the EPM test, 7 days after JWH-018 discontinuation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results contradict some previous studies, given that cannabinoids are understood to be anti-inflammatory and JWH-018 seemed to potentially induce inflammation in Cryab KO mice. However, according to previous studies (Pintori et al, 2021;Margiani et al, 2022), JWH-018 may potentially promote neuroinflammation in mice following previous repeated exposures. Thus, the absence of CRYAB might have exacerbated the neuroinflammatory effect of JWH-018 in Cryab KO mice, resulting in the observed alterations in NF-κB, GFAP, and IL-6 expressions, given also that CRYAB, possessing an anti-inflammatory function, might have rendered the Cryab KO mice susceptible to inflammatory insults.…”
Section: Discussionmentioning
confidence: 87%
“…The results of the SA and CPP tests were consistent with this hypothesis, as WT mice did not exhibit significant preference or tendency for self-administering JWH-018 at 0.03 mg/kg/infusion or 0.3 mg/kg, unlike with previous studies. This discrepancy among studies investigating intravenous JWH-018 SA in WT mice might be attributed primarily to methodological differences, given that some studies required long-term exposure of mice in JWH-018 SA ( de Luca et al, 2015 ), with some using adolescent mice with potentially different drug sensitivity ( Margiani et al, 2022 ). However, the fact that Cryab KO mice exhibited modest SA responses and place preference for JWH-018 indicated cannabinoid-induced addiction-like behaviors, suggesting cannabinoid abuse susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Kevin and colleagues [24] reported decreased IL-1α and IL-12 plasma levels in rats after adolescent treatment with AB-FUBINACA. Recently, our group demonstrated that adolescent voluntary consumption of JWH-018 leads to long-lasting behavioral and neurochemical aberrations along with changes in glial cells (i.e., astrocytopathy and microgliosis) [25]. These glial alterations in adult brains were coupled with an increase in the chemokine regulated on activation normal T cells expressed and secreted (RANTES), a decrease in the cytokines IL-2 and IL-13 in the cortex, and an increase in the chemokine monocyte chemoattractant protein-1 (MCP-1) in the striatum [25].…”
Section: Introductionmentioning
confidence: 99%